Identification and expression analysis of putative mRNA-like non-coding RNA in Drosophila. - Inagaki, S.; Numata, K.; Kondo, T.; Tomita, M.; Yasuda, K.; Kanai, A.; Kageyama, Y. (Genes to cells : devoted to molecular & cellular mechanisms, 2005)
One of the most surprising results to emerge from mammalian cDNA sequencing projects is that thousands of mRNA-like non-coding RNAs (ncRNAs) are expressed and constitute at least 10% of poly(A)(+) RNAs. In most cases, however, the functions of these RNA molecules remain unclear. To clarify the biological significance of mRNA-like ncRNAs, we computationally screened 11,691 Drosophila melanogaster full-length cDNAs. After eliminating presumable protein-coding transcripts, 136 were identified as strong candidates for mRNA-like ncRNAs. Although most of these putative ncRNAs are found throughout the Drosophila genus, predicted amino acid sequences are not conserved even in related species, suggesting that these transcripts are actually non-coding RNAs. In situ hybridization analyses revealed that 35 of the transcripts are expressed during embryogenesis, of which 27 were detected only in specific tissues including the tracheal system, midgut primordial cells, visceral mesoderm, germ cells and the central and peripheral nervous system. These highly regulated expression patterns suggest that many mRNA-like ncRNAs play important roles in multiple steps of organogenesis and cell differentiation in Drosophila. This is the first report that the majority of mRNA-like ncRNAs in a model organism are expressed in specific tissues and cell types.